Medicare Advantage Plan Bid Risk Underestimates and Corresponding Insurer Revenues - David Scheinker; Kevin Schulman; Barak Richman; Arnold Milstein; Richard Kronick (Health Services Research, 2026)
ABSTRACT Objective To estimate the extent to which Medicare Advantage (MA) plans underestimate risk, the additional Part A and Part B (A&B) revenue insurers receive as a result, and how this differs across insurers and over time. Study Setting and Design We compared projected risk in plan‐level bids submitted by insurers to the actual plan‐level risk as subsequently reported by the Centers for Medicare and Medicaid Services (CMS). We estimated the additional A&B revenue MA insurers received due to underestimates. Data Sources and Analytical Samples A total of 34,604 MA plans offered by 317 insurers from 2008 to 2020 from MA Bid Data as well as MA enrollment and payment data, all from publicly available CMS sources. Principal Findings From 2008 to 2020, the average ratio of actual risk to projected risk was 1.01 (95% Confidence Interval, 1.009–1.011) and plans received additional A&B revenue of $14.6 billion due to risk underestimates. The fraction of plans with a ratio above 1.0 rose from 45% in the smallest enrollment quintile to 62% in the largest enrollment quintile. Among the 10 largest insurers, Blue Cross Blue Shield Highmark underestimated risk by the largest amount, an average of 3% from 2008 to 2020, generating $272 per member per year in additional A&B revenue, followed by Centene (2.1%, $202/member). Conclusions From 2008 to 2020, MA plans systematically underestimated actual risk, reducing benefits for beneficiaries and generating additional A&B revenue of approximately 1% of premiums. The frequency and magnitude of the underestimates increased with plan size. This additional A&B revenue represents a significant fraction of reported MA profit margins, which averaged approximately 3.5% of premiums over the period. CMS should more closely scrutinize the projected risk scores in the annual bids. The Department of Justice should consider whether systematic risk underestimation is a violation of the False Claims Act.